IT and public sector management in developing countries: Present status and future prospects - Schware, Robert (2000)
Starting off with a listing of advantages and opportunities offered through IT applications in public administration, the author discusses pursuing of e-governance through the instrumentality of Internet. Besides describing Internet's ability to realise inexpensive, easy and open access to vast array of information, along with checking corruption, enhancing accountability and transparency in public administration, he also discusses important issues pertaining to implementation of the new technologies in administration. He then discusses Brazil's SAC ("shopping mall for public services") programme and Andhra Pradesh's IT-based TWINS, CARDS and ICSC programmes (forming part of its SMART governance programmes to prove relevance of IT in changing the traditional nature of public administration and bringing the people and the government close to each other. - Reproduced
Keywords: E governance - Developing countries; Public sector - Developing countries; Information technology - Developing countries; Information technology